Additional records of bathyal ascidians (Tunicata) from the New Caledonia region - Monniot, Françoise (Zootaxa, 2022)
Two expeditions EXBODI (2011) and SPANBIOS (2021) sampled the invertebrate fauna of deep bottoms on each side of New Caledonia. Many ascidians were collected and the most part are already known species. Among the 13 species described and figured, two are new to science. All have typical characters of a deep habitat. Variability of the internal anatomy is described for abundant specimens of the same species from the same location. There is no concordance with the littoral ascidian fauna.